The influence of social proof, product quality, and price on purchasing decisions for beauty products - Rokhman, Abdul; Sabrina, Farah (Jurnal Mantik, 2025)
This study examines the impact of social recommendations by colleagues who also act as influencers, product quality, and price factors on consumer decisions in buying Skintific beauty products in Cirebon City. With a quantitative approach, this study involved 210 respondents, where data was collected through an online survey and analyzed using SPSS software through multiple linear regression techniques, validity tests, reliability, and hypothesis testing. The findings emphasize that social proof has a major role to play in purchasing decisions, followed by product quality and price. Therefore, it is recommended for Skintific marketers to maximize social evidence-based marketing strategies, improve product quality, and set prices that match consumer value perceptions to drive purchase decisions